2012
DOI: 10.1001/archsurg.2012.814
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Laparoscopic Cholecystectomy

Abstract: Study Selection:We reviewed all studies identified through MEDLINE. References were cross-checked to ensure capture of cited pertinent articles. Case reports and series of less than 4 cases were excluded.Data Synthesis: In total we analyzed 49 studies, including 2336 patients. Seven studies consisted of randomized trials and 11 of case-matched control series (compared with SLC). The technical aspects of SILC were not standardized. Median follow-up time was 4 weeks, although 27 stud-ies (55.1%) reported no foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 58 publications
2
55
2
4
Order By: Relevance
“…There are three main approaches mentioned in the literature to perform SILC. One technique uses special purpose-made access devices/ports (like TriPort) for introducing the laparoscope and instruments which are usually roticulating ones [5]. The second technique includes passing 3-mm trocars side by side through the fascia after exposing a vide area through a single umbilical incision [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are three main approaches mentioned in the literature to perform SILC. One technique uses special purpose-made access devices/ports (like TriPort) for introducing the laparoscope and instruments which are usually roticulating ones [5]. The second technique includes passing 3-mm trocars side by side through the fascia after exposing a vide area through a single umbilical incision [6].…”
Section: Introductionmentioning
confidence: 99%
“…6 Additional studies have confirmed there is no benefit conferred from the SILC within the 6, 8 or 24 hours postoperative period. 4,7 In this study, the umbilical port had the highest median pain score and was reported as the site painful for the longest period after the operation.…”
mentioning
confidence: 98%
“…In Hall et al 6 systematic review of studies, they reported similar or worse postoperative pain scores in 10 out of 13 articles comparing the SILC to the SLC. 6 Additional studies have confirmed there is no benefit conferred from the SILC within the 6, 8 or 24 hours postoperative period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Classical laparoscopic cholecystectomy (CLC) involves 4 ports while the most novel 'single port' technique only requires 1 incision on the abdominal wall [2]. The latter technique is thought to decrease surgical trauma and improve cosmesis [3] although there are reports pointing out that CLC is also feasible in terms of cosmesis [4].…”
mentioning
confidence: 99%